2014
DOI: 10.1017/s0950268814001976
|View full text |Cite
|
Sign up to set email alerts
|

Cross-immunity and age patterns of influenza A(H5N1) infection

Abstract: SUMMARYThe age distribution of influenza A(H5N1) cases reported during 2006–2013 varied substantially between countries. As well as underlying demographic profiles, it is possible that cross-immunity contributed to the age distribution of reported cases: seasonal influenza A(H1N1) and avian influenza A(H5N1) share the same neuraminidase subtype, N1. Using a mechanistic model, we measured the extent to which population age distribution and heterosubtypic cross-immunity could explain the observed age patterns in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…This value agrees well with published estimates of population susceptibility (Table 3), with cross-immunity coming from the smallpox vaccination campaigns that ended in the two decades preceding the outbreaks [5]. We also found evidence of pre-existing immunity to influenza A(H5N1) in older individuals; it has previously been suggested that such immunity could result either from prior exposure to H5N1, or from cross-immunity from previous infection with influenza A(H1N1) [27]. In contrast, we estimated that both age groups had similar levels of susceptibility to MERS and influenza A(H7N9).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This value agrees well with published estimates of population susceptibility (Table 3), with cross-immunity coming from the smallpox vaccination campaigns that ended in the two decades preceding the outbreaks [5]. We also found evidence of pre-existing immunity to influenza A(H5N1) in older individuals; it has previously been suggested that such immunity could result either from prior exposure to H5N1, or from cross-immunity from previous infection with influenza A(H1N1) [27]. In contrast, we estimated that both age groups had similar levels of susceptibility to MERS and influenza A(H7N9).…”
Section: Discussionsupporting
confidence: 91%
“…We found that the 95% confidence interval of the joint Table 3. Comparison of our parameter estimates and previously published estimates of R, from studies using single-type models, and S, from studies of vaccination history [5] and seroprevalence [28,29] and models of immune acquisition [27]. distribution of R 0 and S was very broad (S8 Fig.).…”
Section: Application To Real Outbreaksmentioning
confidence: 72%
“…To formally assess the HA imprinting hypothesis alongside previous explanations (1,37) for observed H5N1 and H7N9 age distributions, we developed a set of multinomial models. These models related the probability that a case occurred in a given birth cohort to country- and year-specific demography, and risk factors including age-based risk of exposure to poultry, age-based risk of severe disease or case ascertainment, and reconstructed patterns of first exposure (and hence potential immunological imprinting) to HA or NA subtypes (Table S1).…”
Section: Ha Imprinting Explains Age Distributionsmentioning
confidence: 99%
“…Despite commonalities in their reservoir hosts and epidemiology, these viruses show puzzling differences in age distribution of observed human cases (1,2). Existing explanations, including possible protection against H5N1 among older birth-year cohorts exposed to the neuraminidase of H1N1 as children (3,4) or age biases in exposure to infected poultry (57), cannot fully explain these opposing patterns of severe disease and mortality. Another idea is that severity of H5N1 and H7N9 differs by age, leading to case ascertainment biases (1), but no explanatory mechanism has been proposed.…”
mentioning
confidence: 99%
“…Despite commonalities in their reservoir hosts and epidemiology, these viruses show puzzling differences in age distribution of observed human cases (2,3). Explanations proposed to date, including possible protection against H5N1 from past exposure to the neuraminidase of H1N1 (4,5) and human behavioral factors (such as age bias in exposure to infected poultry) (6)(7)(8), cannot fully explain these opposing patterns of severe disease and mortality. Another idea is that severity of H5N1 and H7N9 differs by age class, leading to case ascertainment bias (2), but no explanatory mechanism has been proposed.…”
Section: Main Textmentioning
confidence: 99%